Vest Product Design Using Remaining Fabric Material As A Motif With Weaving Technique - Annisa Rochmatul Karimah; Ratna Endah Santoso (Journal of Creative Industries and Vocational Innovation, 2025)
This design aims to process leftover fabric from home-made garment factories into a material for making vests using weaving techniques as a motif creation technique. The increase in textile waste is one of the problems that arise due to mass production. Leftover fabrics that are considered to have no value are reused to produce fashion products with aesthetic and functional value. This research focuses on designing a vest using weaving techniques as a motif creation technique that utilizes leftover fabric as a creative solution to reduce textile waste, especially in the home-made garment industry. The design method applied is based on the craft design approach, namely the three-stage, six-step design method by S.P. Gustami. The design method includes the stages of exploration, design, and realization or embodiment of the work. The design of the work produces a vest that combines denim and leftover fabric. This combination creates an attractive design that suits the trends and character of the young generation who are active, creative, and have concern for the environment.